Proton Pump Inhibitors - Clinical Use and Long-Term Safety in Adults - Patrzykąt, Klaudia Martyna; Zakrzewska, Anna Maria; Midera, Aleksander; Leśniak, Julia Aleksandra; Borowski, Michał; Niwińska, Klaudia Elżbieta; Michalak, Julia Agnieszka; Czaplińska-Paszek, Zofia; Leśniak, Natalia Maria; Popielarska, Kinga (Quality in Sport, 2026)
Background. Proton pump inhibitors (PPIs) are widely prescribed for gastrointestinal disorders. Their potent and persistent inhibition of gastric acid ensures efficacy but has raised concerns about adverse effects during long-term therapy. Aim. To summarize current evidence on the indications and clinical benefits of proton pump inhibitors in adults, and to review major long-term adverse effects and drug–drug interactions to guide safer treatment strategies. Material and methods. A narrative literature review was conducted using PubMed/MEDLINE for articles published between January 2016 and November 2025. Peer-reviewed human studies and major reviews on adults receiving oral PPIs were included if they addressed utilization, indications, duration of therapy, long-term adverse effects, drug-drug interactions, or deprescribing strategies. Pediatric studies, purely animal research, and non-peer-reviewed articles were excluded. Results. PPIs remain first-line treatment in gastroesophageal reflux disease, peptic ulcer disease, Helicobacter pylori eradication, and selected hypersecretory conditions. However, many patients receive these medications chronically without a clear ongoing indication or regular reassessment. Long-term PPI therapy can be linked to nutrient and electrolyte disturbances, increased fracture risk, renal complications, infections, and clinically relevant interactions with drugs such as clopidogrel and methotrexate. Cardiovascular and neurological risk signals remain inconclusive. Conclusions. PPIs should not be withheld from patients with justified indications, but must be prescribed thoughtfully. Clinicians need to use the lowest effective dose for the shortest necessary duration, regularly review indications, and educate patients to limit unnecessary chronic exposure while preserving the substantial benefits of PPI therapy.